Spectral domain optical coherence tomography changes following intravitreal dexamethasone implant, Ozurdex ® in patients with uveitic cystoid macular edema - Pooja Bansal (Indian Journal of Ophthalmology, 2015)
Purpose: To correlate the structural and functional changes following intravitreal injection of dexamethasone 0.7 mg (Ozurdex ® ) implant in patients with recalcitrant uveitic cystoid macular edema (CME). Materials and Methods: In a prospective, interventional, nonrandomized study, 30 eyes (27 patients) with uveitic CME received Ozurdex ® implant and were followed-up for 24 weeks at periodic intervals to monitor structural alterations seen on spectral domain optical coherence tomography (SD-OCT). The outcome measures included change in central macular thickness (CMT) and best-corrected visual acuity (BCVA) as well as structural alterations seen on OCT such as change in the height of cystoid spaces (CSs) and sub-foveal serous retinal detachment (SSRD). The integrity of external limiting membrane and inner-outer segment junction was assessed at baseline and follow-up visits. Results: Mean age of the patients was 46.09 ± 15.66 years. The mean CMT decreased by 96 μm at 1-day, 231.64 μm at 1-week, 254.21 μm at 4 weeks and 249.14 μm at 12 weeks (P < 0.001) compared with baseline. BCVA improved from a baseline mean of 0.62 LogMAR units to 0.49 on day 1 to 0.31 at 24 weeks (P < 0.001). A decrease in the mean height of CS, that is, 133.28 μm from a baseline of 317.71 μm was noted on the 1 st day (P < 0.001). 4 eyes demonstrated the presence of CS at 4 weeks, 1 eye at 6 weeks and 3 eyes at 12 weeks. At baseline, 16 eyes (53.33%) demonstrated the presence of SSRD. Among these, 11 eyes showed resolution of SSRD on day 1. SSRD resolved in all patients at 4 weeks and was maintained up to 24 weeks. Conclusions: Ozurdex ® implant improves the visual outcome of patients with recalcitrant uveitic CME. Reversibility of retinal changes may be possible following treatment with dexamethasone implant. Thus final visual outcome may be independent of pretreatment CMT, the height of CS or SSRD.